Հայ-վրացական հարաբերությունները և Բախշի Ւշխանյանը - Անահիտ Բադալյան (ՀՀ ԳԱԱ հրատ.)
Among the publicists of the mid-20 century prominenteconomists Baxshi lshxanyan has his special place. As a well-known publicist he referred to Armenia-Georgian relationship by writing the work “The problem of Armenia-Georgian relationship”. In the work he focusses on the problems between Armenians and Georgians, giving the facts for their reasons.
Keywords: Political Science; International relations